The Blood of Christ Compels Them: State Religiosity and State Population Mobility During the Coronavirus (COVID-19) Pandemic - Hill, Terrence D. (Journal of religion and health, 2020)
This paper examines the association between state religiosity and population mobility during the coronavirus (COVID-19) pandemic. We use first-party geo-behavioral data collected through mobile phone operating systems, global positioning systems, and Wi-Fi signals to assess changes in the average median distance traveled by approximately 15,000,000 devices over eight weeks (February 24-April 13) in the contiguous United States. Robust regression results show that more religious states tend to exhibit higher average mobility scores and slower average declines in mobility. Findings also suggest that state stay-at-home orders have a weaker impact on mobility in more religious states.